Flexitime and Performance of Academic Staff in Polytechnics in North West Geo-Political Zones of Nigeria - Abba, Halilu Dahiru (NIU Journal of Social Sciences, 2018)
The study examined the influence of flexitime on performance of academic staff in polytechnic in North West Geo-Political Zones of Nigeria. The correlational study involved 285 respondents from six polytechnics. Data were collected using a self-administered a questionnaire whose validity and reliability was confirmed through Factor Analysis and Cronbach Alpha test. Descriptive analysis involved the use of means, while multiple regression was used to test the hypotheses. The results revealed that flexitime had a positive and significant influence on performance of academic staff. This led to the conclusion that that flexitime is a significant factor for the performance of academic staff. Therefore, it was recommended that managers of organisations such as polytechnics should establish flexible working arrangements to enhance performance of employees. Keywords: Academic Staff, Employee, Flexitime, Performance, Regression.